Microthermal-induced subcellular-targeted protein damage in cells on plasmonic nanosilver-modified surfaces evokes a two-phase HSP-p97/VCP response - Mistrik, Martin; Skrott, Zdenek; Muller, Petr; Panacek, Ales; Hochvaldova, Lucie; Chroma, Katarina; Buchtova, Tereza; Vandova, Veronika; Kvitek, Libor; Bartek, Jiri (Nature communications, 2021)
Despite proteotoxic stress and heat shock being implicated in diverse pathologies, currently no methodology to inflict defined, subcellular thermal damage exists. Here, we present such a single-cell method compatible with laser-scanning microscopes, adopting the plasmon resonance principle. Dose-defined heat causes protein damage in subcellular compartments, rapid heat-shock chaperone recruitment, and ensuing engagement of the ubiquitin-proteasome system, providing unprecedented insights into the spatiotemporal response to thermal damage relevant for degenerative diseases, with broad applicability in biomedicine. Using this versatile method, we discover that HSP70 chaperone and its interactors are recruited to sites of thermally damaged proteins within seconds, and we report here mechanistically important determinants of such HSP70 recruitment. Finally, we demonstrate a so-far unsuspected involvement of p97(VCP) translocase in the processing of heat-damaged proteins. Overall, we report an approach to inflict targeted thermal protein damage and its application to elucidate cellular stress-response pathways that are emerging as promising therapeutic targets.
Keywords: nádorové buněčné linie; protein obsahující valosin; Valosin Containing Protein; Ubiquitin; vysoká teplota; HSP70 Heat-Shock Proteins; Proteasome Endopeptidase Complex; Single-Cell Analysis; stříbro; Silver; Cell Line, Tumor; proteasomový endopeptidasový komplex; Surface Plasmon Resonance; ubikvitin; Humans; reakce na tepelný šok; Hot Temperature; analýza jednotlivých buněk; Heat-Shock Response; povrchová plasmonová rezonance; proteiny tepelného šoku HSP70; Metal Nanoparticles; kovové nanočástice; lidé